1946
DOI: 10.1103/physrev.70.213
|View full text |Cite
|
Sign up to set email alerts
|

The Inversion Spectrum of Ammonia

Abstract: Ammonia gas is known to exhibit a strong absorption in the region of 0.8 cm" 1 . By sweeping the frequency of a continuous wave oscillator and using a balanced wave guide system with one arm of the wave guide serving as an absorption chamber, thirty lines of the fine structure, as predicted by Sheng, Barker, and Dennison, have been observed in this region. Their intensities and frequencies have been measured for two different temperatures and an empirical expression for the frequencies of the lines in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1948
1948
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…If the potential energy barrier between these two cis configurations is small, such that the molecule can tunnel through it, one has the possibility of inversion-like doubling of the vibrational levels of the two configurations, just as in the familiar case of NH 3 . [5][6][7][8][9] Unlike NH 3 , though, one can take acetylene back to its original configuration by a C 2 rotation about the inertial a-axis, which means that the new configuration is the same as the original one. Since there is only one possible configuration, the energy states of the second configuration must be "thrown away.…”
Section: On the Origin Of The K-staggeringmentioning
confidence: 99%
See 1 more Smart Citation
“…If the potential energy barrier between these two cis configurations is small, such that the molecule can tunnel through it, one has the possibility of inversion-like doubling of the vibrational levels of the two configurations, just as in the familiar case of NH 3 . [5][6][7][8][9] Unlike NH 3 , though, one can take acetylene back to its original configuration by a C 2 rotation about the inertial a-axis, which means that the new configuration is the same as the original one. Since there is only one possible configuration, the energy states of the second configuration must be "thrown away.…”
Section: On the Origin Of The K-staggeringmentioning
confidence: 99%
“…Exactly how the vibrational level structure evolves in this non-symmetric double minimum situation has not been fully established, though the basic ideas follow from the many studies that have been made of simpler, symmetric potential barrier situations such as internal rotation 4 and ammonia-type inversion. [5][6][7][8][9] One of the simplest systems that possesses cis and trans isomers is the first excited singlet electronic state (S 1 ) of acetylene, C 2 H 2 . Ab initio calculations [10][11][12][13][14][15][16][17][18][19][20] predict that the trans isomer is more stable, with the cis isomer lying about 2700 cm −1 higher, and the barrier to isomerization (saddle point) about 2000 cm −1 higher still.…”
Section: Introductionmentioning
confidence: 99%
“…By 1946, Van Vleck and Weisskopf had published a theory of collision broadening of spectral absorption lines (11) and the absorption of microwave energy in gases had been observed for rotational transitions in linear and asymmetric top molecules, (12,13) as well as for low pressure ammonia (13)(14)(15). Also in 1946, Beringer reported observations of microwave absorption in oxygen gas which he attributed to the permanent magnetic dipole of the oxygen molecule (16).…”
Section: Initial Sparks For Epr In a Gasmentioning
confidence: 94%
“…EPR absorption in NO gas was observed to occur as three groups of three lines separated by 27 G with the groups separated by 45 G. But which triplet splitting was due to hyperfine coupling? When we generated the NO gas from a source material which had been enriched with 15 N (I = V-i) a weak line from 15 NO molecules appeared within each of the 27 G splittings, establishing the 27 G splitting as hyperfine coupling to 14 N (21). Beringer, Rawson, and Henry measured the NO spectrum at lower pressure and reinterpreted the intensity of the EPR lines as being principally from the electric dipole within NO interacting with the microwave electric field throughout the cavity (22).…”
Section: Stable Paramagnetic Gasesmentioning
confidence: 99%
“…Einstein and Ehrenfest (5) discussed the possibility of inducing magnetic transitions between magnetic sublevels, and Dorfinan (6) proposed the possibility of resonance absorption of electromagnetic waves by paramagnetic materials. In 1924 Pauli (7) suggested that the hyperfine structure observed in atomic spectra arose because atomic nuclei possessed magnetic moments which interacted with 14 Foundations of Modem EPR the orbital electrons of the atoms. During the early 1930's the magnetic moment of the proton was measured with an accuracy of 10% by using a beam of hydrogen molecules (8).…”
Section: Molecular Beams and Predictions Of Resonant Absorptionmentioning
confidence: 99%